The Role of Guidance and Counseling in Overcoming Student Delinquency at Madrasah Aliyah Azkiya Al-Islami Ciheulang - Redmon Windu Gumati; Ucu Cahya (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2024)
The delinquency that occurs in Madrasahs is the behavior of students before entering the Madrasah, meaning that bad behavior before they enter the madrasah is sometimes still carried over and causes Guidance and Counseling (BK) delinquency to recur when they enter the school/madrasah, because the position of the Madrasah is as a religious place where Of course, the character of the students will be shaped religiously, many of the students live in environments that have bad relationships and bring their bad behavior into the school/madrasah environment. In dealing with student delinquency, guidance and counseling teachers have a different role from guidance and counseling teachers in general, where the counseling guidance activity program is very influential with the presence of the madrasa head, decisions taken by guidance and counseling teachers must be agreed upon by the head of the madrasa. In giving punishment, the supervising teacher is only free when students commit violations in the light category, apart from two categories of violations, namely moderate and serious violations, the supervising teacher must report the case to the head of the madrasah. So in cases of moderate and serious delinquency, the supervising teacher only acts as a monitor or supervisor, not as an executor or person who has great authority in giving sanctions. All actions of the supervising teacher must be coordinated first with the head of the madrasah. The sanctions given by guidance and counseling teachers are basically sanctions that have been made by all elements of the madrasah, from the madrasah principal, deputy madrasah principal, supervising teachers and other teachers' councils.